Risk of macrovascular complications in statin-treated patients developing diabetes. (November 2019) - Chen, Yin-Huei; Yang, Yu-Cih; Chen, Weishan; Lin, Yen-Nien; Hung, Yi-Chih
Abstract: Aims: To assess the risk of macrovascular complications in patients developing diabetes from statin treatment. Methods: In this population-based cohort study, 40, 409 participants who began to receive statin therapy between 2000 and 2012 were enrolled in to the study group, and another 1:1 matched adults without statin treatment during the same period served as the control group. Both groups were followed up to identify individuals who later developed diabetes. After a follow-up identification of diabetes, diabetes and non-diabetes cohorts were subjected to an analysis for the risk of macrovascular events between diagnosis of diabetes and December 31, 2013. Results: Compared with individuals without statin therapy, statin-treated patients had a higher risk of developing diabetes (adjusted hazard ratio: 2.46; 95% confidence interval: 2.37–2.57). Compared with statin-treated patients without diabetes, statin-treated participants developing diabetes had a higher overall incidence of macrovascular complications (adjusted hazard ratio: 1.74; 95% confidence interval: 1.62–1.88). Moreover, compared with that of other diabetogenic statins, patients taking pravastatin had a lower risk of developing diabetes (adjusted hazard ratio: 0.63; 95% confidence interval: 0.55–0.73) and macrovascular events (adjusted hazard ratio: 0.64; 95% confidence interval: 0.42–0.98). Conclusions: According to these findings, prescribing statins that have a neutral effect on glucose homeostasis may be advisable for Asian populations.